2005
DOI: 10.1242/jcs.02320
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic tail sequences and subunit interactions are critical for synaptic localization of glutamate receptors

Abstract: AMPA-type glutamate receptors mediate excitatory synaptic transmission in the nervous system. The receptor subunit composition and subcellular localization play an important role in regulating synaptic strength. GLR-1 and GLR-2 are the Caenorhabditis elegans subunits most closely related to the mammalian AMPA-type receptors. These subunits are expressed in overlapping sets of interneurons, and contain type-I PDZ binding motifs in their carboxy-terminal cytosolic tail sequences. We report that GLR-1 and GLR-2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 49 publications
(81 reference statements)
2
27
0
Order By: Relevance
“…This result is in agreement with the finding that the proximal 39 aa of GluR1 tail are sufficient for dendritic targeting in vertebrate neurons (51). The juxtamembrane 30 aa of GLR-1 contain a proximal, highly conserved 12 aa sequence that is present in vertebrate glutamate receptors (37). This highly conserved sequence has been found to be critical for AMPA-stimulated GluR2 endocytosis in HEK cells (53), and for endocytosis and endocytic sorting of NMDA receptors (54).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result is in agreement with the finding that the proximal 39 aa of GluR1 tail are sufficient for dendritic targeting in vertebrate neurons (51). The juxtamembrane 30 aa of GLR-1 contain a proximal, highly conserved 12 aa sequence that is present in vertebrate glutamate receptors (37). This highly conserved sequence has been found to be critical for AMPA-stimulated GluR2 endocytosis in HEK cells (53), and for endocytosis and endocytic sorting of NMDA receptors (54).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, this region of glutamate receptor C termini appears crucial for various endocytic and exocytic processes, as well as interactions with the cytoskeleton. Interestingly, distal C-terminus PDZ motifs of AMPA-type glutamate receptors have been implicated in their synaptic clustering/retention in both vertebrates (58,59) and in C. elegans (26,37). Yet, these PDZ motifs are not required for glutamate receptor dendritic targeting (51, and this study), suggesting that molecular mechanisms specifying ''global targeting'' (to the dendrite) and ''local targeting'' (to the synapse) are at least partly distinct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies showed that a point mutation in this PDZ-ligand of GluR1 (GluR1T887A) blocked interactions with PDZ proteins (Cai et al 2002) and prevented longterm potentiation (LTP) and CaMKII-induced potentiation in organotypic hippocampal slices . Subsequent studies with this GluR1 (T887A) mutant in dissociated cultured neurons (Passafaro et al 2001), hippocampal slice cultures (Piccini and Malinow 2002), or Caenorhabditis elegans in vivo (Chang and Rongo 2005) also found receptor trafficking deficits. In contrast, a recent study using a mouse knock-in model showed that removal of the last seven amino acids of GluR1 (GluR1⌬7) does not affect receptor incorporation into synapses or LTP .…”
mentioning
confidence: 94%
“…PDZ domains play critical roles in protein-protein interactions for many cellular processes (Garner et al 2000;Kim and Sheng 2004). The GluR1 C-terminal PDZ-ligand domain is conserved among humans (TGL), rodents (TGL), birds (TGL), fish (SGM), and worms (TLF), suggesting that this region is important for GluR1 function (Chang and Rongo 2005). Early studies showed that a point mutation in this PDZ-ligand of GluR1 (GluR1T887A) blocked interactions with PDZ proteins (Cai et al 2002) and prevented longterm potentiation (LTP) and CaMKII-induced potentiation in organotypic hippocampal slices .…”
mentioning
confidence: 99%